Cytochemical analysis of cerebrospinal fluid in tuberculous meningitis versus other etiologies - Hueda-Zavaleta, Miguel; de la Torre, Juan C. Gómez; Barletta-Carrillo, Claudia; Tapia-Sequeiros, Gustavo; Flores, Cinthya; Piscoche, Cristian; Miranda, Cecilia; Mendoza, Ada; Sánchez-Tito, Marco; Benites-Zapata, Vicente A. (PLOS ONE, 2025)
Background Meningeal tuberculosis (TBM) is the most severe form of extrapulmonary tuberculosis due to its high mortality and long-term sequelae in survivors. Methods A cross-sectional study of diagnostic tests was carried out in a private clinical laboratory in Lima, Peru. All cerebrospinal fluid (CSF) samples from patients with suspected meningitis were analyzed with cytochemical and biochemical studies, as well as smear microscopy, India ink, the FilmArray Meningitis/Encephalitis panel, Xpert® MTB/RIF or Xpert MTB/RIF Ultra, and culture for common bacterias, fungi or mycobacterial. Results 450 CSF samples were included. The main microorganisms detected were Mycobacterium tuberculosis (8.9%), Cryptococcus neoformans (6.0%), and Streptococcus pneumoniae (2.4%). 97.5% of patients with TBM presented positive Xpert MTB/RIF or Ultra. The median number of red blood cells, leukocytes, and percentage of mononuclear cells, glucose, and proteins in the CSF was 57.5 cells/μl, 91.5 cells/μl, 70%, 22.5 mg/dL and 218.3 mg/dL, respectively. Likewise, patients with TMB had the lowest glucose levels (median: 22.5, IQR: 11 - 35) compared to other etiologies of meningitis. While bacterial meningitis had the highest leukocyte (median: 173 μl; IQR: 17 - 520) and protein levels (median: 289.7; IQR: 92 - 556). Conclusion The characteristics of the cytochemical study of CSF can guide the differential diagnosis by identifying general trends of tuberculous meningitis and other meningitis etiologies. However, it remains necessary to establish methods with greater precision to properly define the etiological agent causing meningitis.